(untitled) (Journal of Parents and Teachers, 2014)
The following article deals with the historical development of access and incorporation of the social worker and counselor at school. Both roles play within the school and what its main features are. In addition, it says what the network of educational guidance is , what aspects are working, what kind of student is and how such elementary points in the work of these members of the educational community.